Onset and transition of and recovery from adverse development: Study methodology. Issue 5 (5th November 2019) - Wigman, Johanna T.W.; Pijnenborg, Gerdina H.M.; Bruggeman, Richard; Vos, Maarten; Wessels, Anita; Oosterholt, Inez; Nauta, Maaike; Stelwagen, Renee; Otto, Lana; Wester, Anniek; Wunderink, Lex; Sportel, Esther; et al.
Abstract: Aim: Early intervention programs for first‐episode psychosis have led to the awareness that the period before onset of a first episode is important in light of early intervention. This has induced a focus on the so‐called 'at risk mental state' (ARMS). Individuals with ARMS are at increased risk for later psychotic disorder, but also for other psychiatric disorders as well as poor psychosocial functioning. Thus, adequate detection and treatment of ARMS is essential. Methods: Since 2018, screening for and treatment of ARMS is recommended standard care in the Netherlands. Implementation is still ongoing. We initiated a naturalistic long‐term cohort study of ARMS individuals, the onset and transition of and recovery from adverse development (OnTheROAD) study, with the aim to monitor course and outcome of symptoms and psychosocial functioning over time, as well as patterns of comorbidity and associations with factors of risk and resilience. To this end, participants complete a broad battery of instruments at baseline and yearly follow‐up assessments up to 3 years. Outcome is defined in terms of symptom severity level, functioning and quality of life. In particular, we aim to investigate the impact of negative symptoms as part of the ARMS concept. Results from this study can aid in refining the existing ARMS criteria, understanding the developmental course of ARMS and investigating the hypothesized pluripotentiality in outcome of ARMS. New knowledge may inform the further development of specialized early interventions. Results and Conclusions: In this article, we describe the rationale, outline and set‐up of OnTheROAD.